Propuesta de aplicación del e-commerce para la empresa Nicomar Electronics S.A (2021)
Companies have benefited from the implementation of e-commerce, as they see the opportunity to reach their customers more easily, because more and more people choose to make their purchases over the internet, this scenario raises an opportunity for companies to address this population by lowering costs by having a commercial establishment elsewhere, we aim that with the implementation of a B2B (Business-to-Business) e-commerce system, the company demands a system that centrally manages and automates all order and quote processes, customers are required to always have the status information of their orders, inventory, product data sheet, online payments , this investigation will allow us, analyze the advances and challenges that the implementation